Dietary Arginine Modulates Growth Performance, Hemato-Biochemical Indices, Intestinal Enzymes, Antioxidant Ability and Gene Expression of TOR and 4E-BP1 in Rainbow Trout, Oncorhynchus mykiss Fingerlings - Ahmed, Imtiaz; Ahmad, Ishtiyaq; Malla, Bashir Ahmad; Shah, Basit Amin; Wani, Zubair Ahmad; Khan, Younis Mohd (Frontiers in Marine Science, 2022)
We evaluated the effect of arginine on growth, hemato-biochemical variables, intestinal enzymes, antioxidant ability, and expression of target of rapamycin (TOR) signaling pathway related genes in fingerling Oncorhynchus mykiss. A series of six uniform diets consisting of 450 g kg-1 of protein and 20.9 g-1 of energy with graduated levels (10.0, 12.5, 15.0, 17.5, 20.0, and 22.5 g kg-1) of arginine were formulated. Significant (p < 0.05) variations were observed in various analyzed parameters. Growth parameters showed a positive linear trend with increasing arginine levels up to 17.5 g kg-1. Fish offered 17.5 g kg-1 of dietary arginine exhibited highest body protein, lowest moisture, and intermediate fat contents, whereas, body ash content did not significantly (p > 0.05) change with respect to each dietary arginine offered diet, except for the lowest levels. Each group also produced significant (p < 0.05) changes in their hematological variables with maximum hemoglobin (Hb), hematocrit (Hct) content, and red blood cell (RBC) count noted at 17.5 g kg-1 arginine diet. Although the majority of blood plasma parameters were insignificantly (p > 0.05) different with respect to varied arginine fed diets, plasma aspartate transaminase (AST) showed significant (p < 0.05) variations across the treatments. Moreover, total protein, alkaline phosphatase (ALP) and albumin contents increased significantly (p < 0.05) with increasing arginine concentrations up to 17.5 g kg-1 and, thereafter, a declined trend in these parameters were noted. Intestinal enzymes and antioxidant properties showed significant (p < 0.05) variations, except plasma amylase, which showed insignificant variation. The maximum up-regulation of TOR and 4E-BP1 gene expression levels were found for fish fed 17.5 g kg-1 of dietary arginine compared to the lower (10.0 and 12.5 g kg-1) and higher (20.0 and 22.5 g kg-1) arginine levels, which indicates that fish utilize arginine more efficiently at this point. Quadratic regression analysis of live weight gain (LWG), feed conversion ratio (FCR), protein efficiency ratio (PER) and body protein deposition (BPD) indicated the optimal arginine requirement of rainbow trout to be 17.61 g kg-1 of dry diet, corresponding to 39.13 g kg-1 of dietary protein, which enhances growth, immunity, antioxidant ability, and also promote TOR signaling pathway in rainbow trout.